2018
DOI: 10.1186/s41016-018-0131-x
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle screw accuracy assessment in ExcelsiusGPS® robotic spine surgery: evaluation of deviation from pre-planned trajectory

Abstract: Background: The ExcelsiusGPS® (Globus Medical, Inc., Audubon, PA) is a next-generation spine surgery robotic system recently approved for use in the United States. The objective of the current study is to assess pedicle screw accuracy and clinical outcomes among two of the first operative cases utilizing the ExcelsiusGPS® robotic system and describe a novel metric to quantify screw deviation. Methods: Two patients who underwent lumbar fusion at a single institution with the ExcelsiusGPS® surgical robot were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 22 publications
2
38
0
Order By: Relevance
“…We find a very high accuracy as shown in bone entry deviation data and angular errors (0.48 ± 0.44 mm, 0.94 ± 0.83° and 0.68 ± 0.58 mm, 0.87 ± 0.82°) in the axial and sagittal planes, respectively. This is in line with top performers among previously published material on bone entry deviation accuracy and superior in regard to angular errors (Table 3) [30][31][32][33][34][35][36] . This in turn resulted in a favorable simulated Gertzbein grading (100% accuracy), well in line with the vast majority of recent studies that typically report 98 -100% accuracy 34,[37][38][39][40][41] .…”
Section: Discussionsupporting
confidence: 89%
“…We find a very high accuracy as shown in bone entry deviation data and angular errors (0.48 ± 0.44 mm, 0.94 ± 0.83° and 0.68 ± 0.58 mm, 0.87 ± 0.82°) in the axial and sagittal planes, respectively. This is in line with top performers among previously published material on bone entry deviation accuracy and superior in regard to angular errors (Table 3) [30][31][32][33][34][35][36] . This in turn resulted in a favorable simulated Gertzbein grading (100% accuracy), well in line with the vast majority of recent studies that typically report 98 -100% accuracy 34,[37][38][39][40][41] .…”
Section: Discussionsupporting
confidence: 89%
“…Recently, there was 1 small case series published examining the use of ExcelsiusGPS in 2 patients, demonstrating 100% accuracy in screw placement in 8 screws. 12 This finding is further confirmed with the present study demonstrating 100% accurate screw placement in the subgroup analysis of 66 screws. Similarly, a recent study examining the feasibility of another robotic-navigation guided system, Mazor X (Mazor Robotics Ltd) reported an accuracy rate of 98.7% examining 75 screws.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, placement of 4 additional screws was attempted robotically, but these attempts were aborted due to technical difficulties. 18,19 No prospective, randomized studies of the ExcelsiusGPS have been reported, although initial case reports and small case series indicate high accuracy and safety with rates similar to those of other robotic systems (Figure 2). 15,18,[28][29][30] Additionally, with spinal robotics, the accuracy of screw placement can be judged not only with the conventional GRS but also by measuring deviation from a pre-planned trajectory.…”
Section: Accuracy Of Pedicle Screw Placementmentioning
confidence: 99%
“…In this study, placement of 4 additional screws was attempted robotically, but these attempts were aborted due to technical difficulties. 18,19…”
Section: Current State Of Robot-assisted Minimally Invasive Spinal Sumentioning
confidence: 99%
See 1 more Smart Citation